ASSESSING ROMANIA'S FOOD SECURITY STATUS IN 2022: A COMPARATIVE ANALYSIS WITH REGIONAL PEERS - Maria BOBEICĂ; Georgiana Armenița ARGHIROIU; Silviu BECIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Food security, defined as the availability, accessibility, utilization, and stability of food, is a critical concern in the context of global sustainability and human well-being. The COVID-19 pandemic has further exacerbated existing challenges, putting additional strain on food systems and exacerbating vulnerabilities. The current world status demands a thorough evaluation of the food security situation in Romania and other Eastern European countries. We must take into account various elements that influence this extremely intricate subject. Our approach involves analyzing data from reputable sources whose main purpose is to support nations in finding solutions for a sustainable future, such as FAO, EU or UN. Our goal is to acquire a detailed insight into how world events impacted the food security of Eastern European countries. Moreover, we investigated the role of social and economic inequalities that contribute to food insecurity, as well as the consequences of climate change on food systems' stability. Through this rigorous analysis, we seek to contribute to the existing body of knowledge and inform policy and decision-making processes towards achieving sustainable and resilient food security in the region.